Pearl Millet Technology Adoption and Impact Study in Maharashtra - Charyulu, D. Kumara; Shyam, D. Moses; Bantilan, Cynthia; Borikar, S. T.; Gupta, S. K.; Rai, K. N. (International Crops Research Institute for the Semi-Arid Tropics, 2017)
The area under pearl millet cultivation in Maharashtra is concentrated in nine districts, and together they have more than 90% share in area and production of pearl millet. The coverage of pearl millet area in Maharashtra by improved cultivars was near total. In this background, the present study was taken up to assess the adoption of hybrids and improved varieties and their impact on the incomes and living standards of farmers through a detailed survey of 360 sample households drawn from 60 villages belonging to 20 tehsils from nine districts. The sample for the field survey was concentrated in Nashik, Ahmednagar and Beed districts, with lower allocations to Aurangabad, Pune, Dhule, Jalgaon, Sangli and Satara districts. Three-fourths of the sample farmers belonged to Western Maharashtra (WMH) region and the remaining one-fourth to the Marathwada (MTW) region. The field survey was carried out during 2013 and the household data pertained to the cropping year 2012-13.